Uma “severa doçura”: Esforço e interesse em educação - Simões, António (2010)
According to the opinion presented and discussed in this paper, a severe shortcoming of current education consists of assigning a minor role to effort, both in family education and in school education. In order to show that effort is a not-to-be by-passed factor in education, the point of view of some of the most note-worthy pedagogues is presented and based on it we argue that interest does not replace effort, but rather that it energizes and calls for it.